ANTARA BUNDO KANDUANG “FEMINIM” DAN REALISTIS DI MINANGKABAU - Helfi Helfi; Dona Afriyani (AGENDA: Jurnal Analisis Gender dan Agama, 2019)
This research background lies on various chances of strategic sectors in society without differentiating gender. The research purpose is to figure out the reposition of Feminist Bundo Kanduang to realistic Bundo Kanduang. Literary synthesis research and observation were conducted in this research. The research findings reflect there was reposition of Feminist Bundo Kanduang to realistic Bundo Kanduang in terms of the theme of Kaba and Novel in Minangkabau, the existence of Bundo Kanduang in politics and Pers in Minangkabau, and the roles of Bundo Kanduang in Education